1988
DOI: 10.1148/radiology.167.3.3363138
|View full text |Cite
|
Sign up to set email alerts
|

Tears of the anterior cruciate ligament and menisci of the knee: MR imaging evaluation.

Abstract: In 242 of 3,000 patients who underwent magnetic resonance (MR) imaging of the knee between September 1986 and August 1987, original MR imaging reports were compared with subsequent arthroscopic reports to determine the value of MR imaging in the evaluation of suspected meniscal and complete tears of the anterior cruciate ligament. The overall accuracy for the menisci was 93% (sensitivity, 95%; specificity, 91%) with a false-negative rate of 4.8%. For the anterior cruciate ligament the overall accuracy was 95%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
137
1
9

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(160 citation statements)
references
References 0 publications
8
137
1
9
Order By: Relevance
“…1). The MR findings in ACL rupture (criterion 2), trabecular trauma (criterion 3), and meniscal tear (criterion 4) have been well described in the literature [1,2,12]. Discontinuity (criterion 5) was defined as focal absence or more diffuse non-visualization of normal low signal ligamentous fibers (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1). The MR findings in ACL rupture (criterion 2), trabecular trauma (criterion 3), and meniscal tear (criterion 4) have been well described in the literature [1,2,12]. Discontinuity (criterion 5) was defined as focal absence or more diffuse non-visualization of normal low signal ligamentous fibers (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…All these cases had history of trauma and were associated with multiple injuries. This suggests presence of a single injury should prompt the examiner to look for other subtle associated injuries, which was further confirmed by Mink JH et al [18] They observed on MRI and arthroscopy of 11 patients who had tear of ACL, 7 patients had tear of MCL, 4 patients had tear of lateral meniscus and 1 patient had tear of medial meniscus. In our study grade I tear (64 %) of MCL were more common and followed by grade III tear (20 %).…”
Section: Discussionmentioning
confidence: 63%
“…Additionally, MRI is highly accurate in diagnosing ACL tears and the most appropriate screening tool short of diagnostic arthroscopy, with sensitivity and specificity of over 95%. 5,10,14,16 Nonetheless, it is not economically feasible for every patient to have the benefit of these research reference standards to assist in detecting this injury's presence, which is why the accuracy of manual assessment techniques are of the utmost importance.…”
Section: Limitationsmentioning
confidence: 99%